Informality and Profitability : Evidence from a New Firm Survey in Ecuador - Medvedev, Denis; Oviedo, Ana Maria (World Bank, Washington, DC, 2013)
This paper estimates the impact of informality on firm profits using a new firm-level survey designed specifically for this study. The survey was administered to about 1,200 firms with 50 employees or less in Ecuador's two largest cities, Quito and Guayaquil, plus two main centers of economic activity near the northern and southern borders. The paper's results confirm that the extent of firms' compliance with a set of regulatory requirements is linked to the perceived costs and benefits of informality, such as the probability of detection by the authorities and the likelihood of being fined. Nonetheless, taking into account the non-random placement of firms along the formality-informality spectrum and controlling for a large set of firm, owner, and location characteristics, the paper finds that more formal firms tend to be more profitable and have higher output per worker. This impact operates, inter alia, through more formal firms' ability to obtain improved access to credit and achieve higher sales by issuing receipts to clients.